The Impact of Nurse-Patient Communication on Patient Satisfaction and Outcomes - Hala Dakeelalah Saleh Alsofiany; Reem Mohammed Sulaiman Aljohani; Amirah Metrik Alotaibi; Khalid Abdulkarim Althagafi; Huda Ayed Raheel Alanzi; Saad Saleh Zidan Alanazi; Ali Bin Awadh Bin Summan Alasmari; Sultan Oudah Husain Altowairqi; Nusaybah Ismail Harun Hawsawi; Hadeyah Nasser Othman Hefdi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Effective communication between nurses and patients is a fundamental aspect of nursing practice that significantly impacts patient satisfaction and healthcare outcomes. This paper explores the importance of nurse-patient communication, focusing on how communication strategies influence patient perceptions of care, adherence to treatment plans, and overall health outcomes. By reviewing existing literature and evidence-based practices, this manuscript highlights the key components of nurse-patient communication that foster trust, enhance the therapeutic relationship, and improve patient outcomes. Additionally, it examines barriers to effective communication and the role of healthcare systems in supporting nurses to develop strong communication skills. Ultimately, this paper emphasizes the critical role of communication in ensuring high-quality patient care, satisfaction, and improved health outcomes.